STUDI KUAT TEKAN BETON DENGAN AGREGAT KASAR DARI BATU KAPUR - Hartono, Hartono (Vocational School Diponegoro University, 2013)
Hartono, in this paper explain that to obtain the allowed characteristic compressive strength of concrete from a concrete construction is quite difficult , because it is influenced by the mix of materials used for the manufacture of the construction, in which the require material of the concrete mix had to be in accordance with Reinforced Concrete Indonesia Rule Year 1991.Â The main factor of mix material that affect permitted the compressive strength of concrete is aggregate characteristics, namely the coarse aggregate or crushed stone. Therefore this study is intended to determine the compressive strength of concrete with the characteristics of coarse aggregate material of crushed stone that comes from limestone. This research use Gresik PC mixture concrete, muntilan sand, and kricak of limestone. To determine concrete compressive characteristics strength of concrete, concrete specimen as many as 20 pieces, with mixed-use PC weight ratio of 1 : 2 Ps : 3, cube molded kricak with the size of 15 cm X 15 cm X 15 cm was made. From these results, it can be obtained that concrete compressive characteristic strength Ïƒ 1 bk = 215.41 kg / cm2. Keyword: Concrete construction